From form features to semantic features in existing MCAD: An ontological approach. (April 2020) - Mandorli, Ferruccio; Borgo, Stefano; Wiejak, Paulina
Abstract: Today's product development processes rely on Mechanical Computer-Aided Design (MCAD) systems that implement a geometric-centered perspective in design. The development of long discussed feature-based MCAD has not yet led to systems that truly support semantic and functional representation of features, which hampers also the use of these models for functional reasoning. This paper investigates the present feature-based MCAD limitations. It illustrates, through simple examples, how to use ontological analysis and feature re-classification to introduce software extensions in existing MCAD that achieve a newer level of semantic representation of features, and enhance the cognitive understanding of the final model. The proposal also shows how to automatically validate these features from the functional viewpoint.